Who is happier among preclinical medical students: the impact of chronotype preference. (2nd August 2020) - Tan, Makbule Neslisah; Mevsim, Vildan; Pozlu Cifci, Merve; Sayan, Huseyin; Ercan, Anıl Emre; Ergin, Omerul Faruk; Oksuz, Umut; Ensari, Salih
ABSTRACT: Most studies and systematic reviews of the psychological health of medical students have investigated the negative aspects of depression and anxiety. Evidence from several studies suggests depressive symptoms are common in medical school students. Moreover, evening chronotype is considered a risk factor for the development of depression. However, surprisingly no study has assessed the possible relationship between chronotypes and happiness. The aims of this study were to: (a) assess happiness and its predictors among Turkish preclinical medical students, (b) identify chronotype preferences, and (c) determine whether these predictors mediate the relationship between chronotype and happiness. Sociodemographic and clinical data collection form, Oxford Happiness Questionnaire short form (OHQ-SF), and Morningness-Eveningness Questionnaire (MEQ) were used to collect data. In this cross-sectional study, 564 students in their pre-clinical year properly completed the questionnaires. The mean age was 19.89 ± 1.37 years (range: 17–26 years). The mean total OHQ-SF score was 23.09 ± 4.23. Female students were significantly happier than male students ( p =.042). Thirty-eight (6.7%) students were morning type, 376 (66.7%) were intermediate type, and 150 (26.6%) were evening type. The distribution of chronotypes did not differ by gender ( p =.085). Evening types showed significantly lower OHQ-SF scores than morning ( p <.001) and intermediate types ( p <.001). MEQ scores were positively correlated with OHQ-SF scores (Pearson, r =.245, p <.001). Multivariate analyses showed that gender, perceived economic resources, physical activity, depression diagnosed the previous 12 months, stressful life events and chronotypes were predictors of happiness among Turkish preclinical medical students. These six variables explained 15% of the total variance of happiness. In conclusion, this study identified evening-type individuals showed less happiness in comparison to the morning-type and intermediate-type individuals. There was a significant relationship between happiness and chronotype, even when controlling for confounding variables, such as age, gender, and others. This information could have clinical implications and contribute to chronobiological approaches for the protection of psychological health.